Time Management, Human Resource Management, Career Development as Predictors of Job Satisfaction - Novi Hidayat; Rismawati Rismawati; Ziyadi Ali Ikromi; Abdul Kodir; Wisnu Surya (The Eastasouth Management and Business, 2026)
At the heart of an organization's success is a key yet often overlooked factor: employee job satisfaction. More than just comfort, it reflects how deeply employees feel valued, supported, and given room to grow. When managed well through effective time use, fair HR practices, and clear career paths satisfaction fuels greater productivity, loyalty, and retention. This research seeks to investigate the roles of time management, human resource management (HR), and career development as determinants of employee job satisfaction. Employing a quantitative methodology, the study utilized a survey conducted among a diverse group of employees across various industries, yielding a total of 109 respondents through non-probability and purposive sampling techniques. The research findings show a significant influence between human resource management, time management, and career development on job satisfaction. Furthermore, a contribution of 36% from time management, human resource management (HR), and career development, while the remaining 64% is due to other factors not covered in this study.